Distal catheter lengthening in pediatric patients with hydrocephalus using a guidewire-assisted technique (2020)
Purpose The aim of this study was to evaluate the lengthening or replacement of the peritoneal catheter in a ventriculoperitoneal shunt by using a simple guidewire-assisted technique. Here we report on our experience with this methodology, its indications, caveats, and contraindications. Methods A prospective study was performed in 59 consecutively shunted children who required elective lengthening of the peritoneal catheter (25 females and 34 males, mean 10.5 + 4.2 years). The procedure required an incision of only 1 cm over the distal catheter. The catheter was sectioned, and a soft hydrophilic guidewire was inserted into the exposed end of it, which serves as a route for the guidewire to reach the intraperitoneal space. The procedure was followed by the replacement of the patient’s catheter with one with additional length as considered appropriate, prior to putting additional slots in the last 5 to 8 cm of the new catheter. Results The technique was used in 62 CSF shunts (3 patients had a double derivative system). Fifty-five of the 62 (89%) procedures performed were effective. A conventional peritoneal opening technique was used in the 7 unsuccessful attempts. One patient presented a migration of the abdominal catheter during the first days after surgery. No incident of peritoneal perforation was associated with this technique, nor were any infections or other early or late complications associated with this surgical procedure. Conclusion The technique we propose permits the peritoneal catheter of a derivative system to be lengthened or replaced in a manner that is simple, fast, and safe